Open-Book Versus Closed-Book Tests in University Classes: A Field Experiment - Rummer, Ralf; Schweppe, Judith; Schwede, Annett (Frontiers in Psychology, 2019)
The present field study compared open-book testing and closed-book testing in two (parallel) introductory university courses in cognitive psychology. The critical manipulation concerned seven lessons. In these lessons, all students received two to three questions concerning the content of the respective lesson. Half the participants (open-book group) were allowed to use their notes and the course materials, which had been distributed at the beginning of each class; the other half was not allowed to use these materials (closed-book group). A surprise test conducted in the eighth week demonstrated better results for the closed-book group. Further 6 weeks later, the final module exam took place. A number of questions in this exam concerned the learning matters instructed during the critical seven lessons. Even with respect to these questions, the closed-book group performed better than the open-book group. We discuss these results with respect to two possible explanations, retrieval practice and motivational differences.